Antral follicle count determines poor ovarian response better than anti-mullerian hormone but age is the only predictor for live birth in in vitro fertilization cycles - Mutlu, Mehmet Firat; Erdem, Mehmet; Erdem, Ahmet; Yildiz, Sule; Mutlu, Ilknur; Arisoy, Ozgur; Oktem, Mesut (Springer/Plenum Publishers, 2013)
To determine the predictive value of serum anti-mullerian hormone (AMH) concentrations and antral follicle counts (AFC), on ovarian response and live birth rates after IVF and compare with age and basal FSH. Basal levels of AMH, FSH and antral follicle count were measured in 192 patients prior to IVF treatment. The predictive value of these parameters were evaluated in terms of retrieved oocyte number and live birth rates. Poor responders in IVF were older, had lower AFC and AMH but higher basal FSH levels. In multivariate analysis AFC was the best and only independent parameter among other parameters and AMH was better than age and basal FSH to predict poor response to ovarian stimulation. Addition of AMH, basal FSH, age and total gonadotropin dose to AFC did not improve its prognostic reliability. Area under curve (AUC) for each parameter according to ROC analysis also revealed that AFC performed better in poor response prediction compared with AMH, basal FSH and age. The cut-off point for mean AMH and AFC in discriminating the best between poor and normal ovarian response cycles was 0.94 ng/mL (with a sensitivity of 70 % and a specificity of 86 %) and 5.5 (with a sensitivity of 91 % and a specificity of 91 %), respectively. However, age was the only independent predictor of live birth in IVF as compared to hormonal and ultrasound indices of ovarian reserve. AFC is better than AMH to predict poor ovarian response. Although AMH and AFC could be used to predict ovarian response they had limited value in live birth prediction. The only significant predictor of the probability of achieving a live birth was age.
Keywords: Anti-mullerian hormone; Antral follicle counts; Ovarian response; Live birth